Criteria of Offenses as Part of Ta'zir Penalty [Kriteria Tindak Pidana yang Diancam Hukuman Ta‘Zir] - Misran Misran (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2021)
Abstract: Jarimah is all deeds that are prohibited by God and threatened with hadd and ta'zir punishment. Hadd is the criminal sanctions that have been regulated in such a way in the texts of the Alquran and Al-Hadith, which consist of: hadd for fornication, hadd for qadhaf, hadd for sariqah (theft), hadd for drink, hadd for hirabah (robbery), hadd for al -baghyu (rebellion), and hadd for riddah (apostasy). The seven forms of hadd are the rights of Allah swt. which cannot be changed in future time. The judge in this case only has to decide with authentic evidence that is determined according to Alquran and al-Hadith. Hadd here also includes jarimah qishash/diyat because there is already a limit on the provisions in the texts. Meanwhile, jarimah ta'zir is a crime that is not determined by God, both in the Alquran and Al-Hadith. Therefore, the authority to determine this kind of punishment is ulil amri or the leader for the sake of achieving the benefit of the ummah. There are three criteria for jarimah ta'zir, namely: first, jarimah hudud that does not meet the requirements or there are doubts, second, jarimah qishash that does not meet the requirements or there are doubts, and thirdly, jarimah ta'zir that stands alone, and has nothing to do with jarimah hudud and qishash that do not meet the requirements or there are doubts. Thus, the ta'zir becomes the authority of the leader to determine it and it is also flexible which can change or even be deleted one day because the existence of the ta'zir follows the demands of benefit. Abstrak: Jarimah yaitu segala perbuatan yang dilarang oleh Allah swt. dan diancam dengan hukuman had dan ta’zir. Had adalah tindak pidana dan sanksi pidananya sudah diatur sedemikian rupa dalam nash Alquran dan Al-Hadis, yang terdiri dari: Had zina, had qadhaf, had sariqah (pencurian), had minum, had hirabah (perampokan), had al-baghyu (pemberontakan) dihukum mati, dan had riddah (murtad). Ketujuh bentuk had tersebut merupakan hak Allah swt. yang tidak dapat diubah lagi. Hakim dalam hal ini tinggal memutuskan dengan bukti-bukti otentik yang ditetapkan menurut Al-Qur’an dan Al-Hadis. Had di sini juga termasuk jarimah qishash/diyat, karena sudah ada batas ketentuannya di dalam nas. Sedangkan jarimah ta’zir adalah tindak pidana yang tidak ditentukan oleh Syari’, baik dalam Alquran dan Al-Hadis. Oleh karena itu yang berwenang menentukannya adalah ulil amri atau pemimpin demi tercapainya kemaslahatan umat. Terdapat tiga kriteria jarimah ta’zir, yaitu: pertama, jarimah hudud yang tidak memenuhi syarat atau terdapat syubhat, kedua, jarimah qishash yang tidak memenuhi syarat atau terdapat syubhat, dan yang ketiga, jarimah ta’zir yang berdiri sendiri, tidak ada kaitannya dengan jarimah hudud dan qishash yang tidak memenuhi syarat atau terdapat syubhat. Dengan demikian jarimah ta’zir menjadi kewenangan pemimpin menentukannya. Jarimah ta’zir yang berdiri sendiri bersifat fleksibel yang suatu saat bisa berubah bahkan dihapus, karena keberadaan jarimah ta’zir mengikuti tuntutan kemaslahatan.